2009
DOI: 10.1002/ptr.2851
|View full text |Cite
|
Sign up to set email alerts
|

Stewartia koreanaextract stimulates proliferation and migration of human endothelial cells and induces neovasculizationin vivo

Abstract: Angiogenesis, the growth of new blood vessels from preexisting vasculature, plays an important role in physiological and pathological processes such as embryonic development and wound healing. This study investigated the effects of methanol extracts of Stewartia koreana leaves (SKE) on angiogenesis. Stewartia koreana significantly promoted the proliferation and migration of human umbilical vein endothelial cells in a dose-dependent manner. The SKE induced endothelial cell proliferation in the range of 50 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…e l s e v i e r . c o m / l o c a t e / i n t i m p inhibition of NO production in LPS-stimulated macrophage cells, and inhibition of HIV protease activity [18][19][20]. A number of phytosterols such as α-amyrin, isoquercitrin, and 3-O-β-D-glucopyanosylspinasterol (spinasterol-Glc) were isolated from methanol extracts of S. koreana leaves.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / i n t i m p inhibition of NO production in LPS-stimulated macrophage cells, and inhibition of HIV protease activity [18][19][20]. A number of phytosterols such as α-amyrin, isoquercitrin, and 3-O-β-D-glucopyanosylspinasterol (spinasterol-Glc) were isolated from methanol extracts of S. koreana leaves.…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 99%
“…Globally accepted herbal drugs are thought to be safe and effective, however, more evidence-based confirmation studies are needed. Among the most frequently studied proangiogenic phytochemicals are ginsenosides from Panax ginseng [1], beta-sitosterol from Aloe vera [2], calycosin from Radix Astragali [4], saponins from Panax notoginseng [5] and extracts from Hippophae rhamnoides L. [2], Radix Astragali [6], Puerariae flos [7], Stewartia koreana [8] and Angelica sinensis [9]. Those previous studies are suggested Chinese medicines as formula for treating angiogenesis disease and wound healing.…”
Section: Introductionmentioning
confidence: 87%
“…It was also found that single components of propolis do not have the same antiviral effect as their mixture in the form of bee glue. This is the basis for the conclusion that propolis extracts can be used locally in viral infections [59]. The research done by Shimizu et al indicates that propolis delays growth and progression of skin changes in an early stage of infection with Herpes simplex and does not cause cytotoxic effect [60].…”
Section: Use Of Propolis In Dental Specialtiesmentioning
confidence: 99%